Peroxisomal Proliferator-Activated Receptor β/δ Deficiency Induces Cognitive Alterations - Espinosa-Jiménez, Triana; Busquets, Oriol; Cano, Amanda; Sánchez-López, Elena; Verdaguer, Ester; Parcerisas, Antoni; Olloquequi, Jordi; Auladell, Carme; Folch, Jaume; Wahli, Walter; Vázquez-Carrera, Manuel; Camins, Antoni; et al. (Frontiers in Pharmacology, 2022)
Peroxisome proliferator-activated receptor β/δ (PPARβ/δ), the most PPAR abundant isotype in the central nervous system, is involved in microglial homeostasis and metabolism, whose disturbances have been demonstrated to play a key role in memory impairment. Although PPARβ/δ function is well-established in metabolism, its contribution to neuronal and specifically memory process is underexplored. Therefore, the aim of the study is to determine the role of PPARβ/δ in the neuropathological pathways involved in memory impairment and as to whether a risk factor implicated in memory loss such as obesity modulates neuropathological markers. To carry out this study, 6-month-old total knock-out for the Ppard gene male mice with C57BL/6X129/SV background (PPARβ/δ-/-) and wild-type (WT) littermates with the same genetic background were used. Animals were fed, after the weaning (at 21 days old), and throughout their growth, either conventional chow (CT) or a palmitic acid-enriched diet (HFD). Thus, four groups were defined: WT CT, WT HFD, PPARβ/δ-/- CT, and PPARβ/δ-/- HFD. Before sacrifice, novel object recognition test (NORT) and glucose and insulin tolerance tests were performed. After that, animals were sacrificed by intracardiac perfusion or cervical dislocation. Different techniques, such as GolgiStain kit or immunofluorescence, were used to evaluate the role of PPARβ/δ in memory dysfunction. Our results showed a decrease in dendritic spine density and synaptic markers in PPARβ/δ-/- mice, which were corroborated in the NORT. Likewise, our study demonstrated that the lack of PPARβ/δ receptor enhances gliosis in the hippocampus, contributing to astrocyte and microglial activation and to the increase in neuroinflammatory biomarkers. Additionally, alterations in the hippocampal insulin receptor pathway were found. Interestingly, while some of the disturbances caused by the lack of PPARβ/δ were not affected by feeding the HFD, others were exacerbated or required the combination of both factors. Taken together, the loss of PPARβ/δ-/- affects neuronal and synaptic structure, contributing to memory dysfunction, and they also present this receptor as a possible new target for the treatment of memory impairment.